Preferential Trading Arrangements and Industrial Location. - Puga, D; Venables, A (1997)
This paper considers the locational effects of geographically discriminatory trade policy. A preferential move towards a free trade area pulls industry into the integrating countries. Input-output links between imperfectly competitive firms amplify this effect and, when trade barriers fall below some critical level, may lead to agglomeration with some member countries gaining industry at the expense of others. A hub-and-spoke arrangement favors location in the hub, with better reciprocal access to spoke nations than these have to each other. Further liberaliation induces agglomeration in the hub and may trigger disparities between the spokes.